If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + -20 = 8x + -4 + -7x Combine like terms: 5 + -20 = -15 -15 = 8x + -4 + -7x Reorder the terms: -15 = -4 + 8x + -7x Combine like terms: 8x + -7x = 1x -15 = -4 + 1x Solving -15 = -4 + 1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -15 + -1x = -4 + 1x + -1x Combine like terms: 1x + -1x = 0 -15 + -1x = -4 + 0 -15 + -1x = -4 Add '15' to each side of the equation. -15 + 15 + -1x = -4 + 15 Combine like terms: -15 + 15 = 0 0 + -1x = -4 + 15 -1x = -4 + 15 Combine like terms: -4 + 15 = 11 -1x = 11 Divide each side by '-1'. x = -11 Simplifying x = -11
| 8a-(a-4)= | | 2h-8=10-4h | | 7y-3=3y+25 | | 42+5=71 | | 2ba+3ab= | | 1/2X1/2=2/5 | | logx(20)=3 | | 3y-11=21 | | 3x+m=16 | | -2.8/7 | | factorisemn=m | | 3(2x-1)=x+27 | | 15-4(2a-1)= | | 3(x-4)=24 | | 4cosx+1=0 | | y=9x^3-7x+2 | | 4c-1=-5 | | 12t=howmenylb | | X+7.1=4.1 | | 3p^2-6p=1 | | 187=88-y | | 1+(4*4)-2= | | S+4.1=8.1 | | 1*10= | | n^2/3-n/6 | | 52x+3=1 | | (3/4)n | | y^2/2=32 | | 9a-8+6a-4= | | 2(3-8)+7= | | y=-5+4sinx | | (5)+(-14)= |